Analisis Mikrobiologi Bekasam Ikan Gabus (Channa striata) Identifikasi Bakteri Asam Laktat dan Potensinya sebagai Probiotik - Tassa Tassa; Ardi Mustakim (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Bekasam is a traditional fermented food made from snakehead fish (Channa striata) through spontaneous fermentation with the addition of salt and rice over several days. This fermentation process promotes the growth of indigenous microorganisms, particularly lactic acid bacteria (LAB), which play a crucial role in developing distinctive flavors and potentially providing health benefits. LAB are well-known for their probiotic effects, such as maintaining gut microbiota balance and enhancing immune system function. This study aimed to identify the presence of LAB in bekasam using the Gram staining method. Samples were taken from bekasam that had been fermented for three days. Bacterial isolation was conducted by culturing the samples on appropriate media, followed by Gram staining to observe bacterial morphology and cell wall characteristics under a microscope. Observations revealed a predominance of Gram-positive, rod-shaped (bacillus) bacteria, which are the primary morphological characteristics of LAB. This morphology is consistent with bacterial groups such as Lactobacillus spp., which are commonly found in traditional fermented products. These findings strengthen the assumption that snakehead fish–based bekasam is not only a traditional food source with rich flavors but also has potential as a natural probiotic source. This potential opens opportunities for bekasam to be developed as a functional food that supports digestive health and immune function. Further research is recommended to perform molecular identification to accurately determine bacterial species and to evaluate their probiotic activity in vivo. Thus, bekasam holds not only cultural and culinary value but also added value in the field of health and the functional food industry.